Pengaruh Biaya Lingkungan Dan Pengungkapan Lingkungan Terhadap Profitabilitas - Putri, Nurmila Eka; Khairani, Siti (Universitas Multi Data Palembang, 2024)
This paper aims to examine the effect of environmental costs and environmental disclosure on profitability in mining sector companies on the Indonesia Stock Exchange for the 2019-2022 period. The approach in this study is a quantitative approach with the type of data, namely secondary data. The sampling in this study used a purposive sampling technique so that a sample of 16 companies. The data analysis method used in this study is the multiple linear regression tests. Based on testing, two results are obtained, namely, first, the environmental costs have no effect on profitability. Then the second is the environmental disclosure has an effect on profitability.